Lobular Carcinoma of the Breast Metastatic to the Spleen and Accessory Spleen: Report of a Case - Gabriel M. Groisman (Case Reports in Pathology)
Despite the fact that accessory spleen (also known as supernumerary spleen, splenunculus, or splenule) can be found in 10–30% of patients undergoing autopsies, metastatic disease occurring in this organ has been barely reported. A case of lobular breast carcinoma metastatic to the spleen and accessory spleen found incidentally at therapeutic splenectomy for severe anemia and thrombocytopenia is described. On microscopic examination both organs revealed severe fibrocongestive changes and extramedullary hematopoiesis with no obvious carcinomatous involvement. Cytokeratin 7, estrogen receptors, and GATA3 immunohistochemistry disclosed the presence of numerous metastatic breast carcinoma cells infiltrating the splenic parenchyma. This case demonstrates that metastatic carcinoma can be encountered, although rarely, in accessory spleens and that cytokeratin stain should be performed in sections of spleens and/or accessory spleens excised from cancer patients in which the presence of malignant epithelial cells is not recognized on routine sections.